Pengujian Kinerja Jaringan Topologi STAR dengan Switching: Studi Simulasi Menggunakan Cisco Packet Tracer - Ardian Nurarifin; Rachmatul Hidayathika; Fiana Fiana; Rafika Desfiana; Didik Aribowo (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
In the present day, many have used communication tools to share data as text, video, images, or sound and the like. There is a speed of data transmission depending on the delivery method, if there is a system error then the data is likely not to be sent, therefore there are various types of data managers so that there are no obstacles or errors during the data transmission process. The star topology was chosen for its advantages in network management, trouble shooting and providing reliable and easy-to-organize connectivity. The main focus is to evaluate the efficacy and effeciency of the star topology in handling different amounts of data traffic using performance characteristics including packet loss, jitter, delay, and throughput. And the use of switching in the star topology can provide optimal and stable performance under high traffic load can provide reliability and efficiency in data traffic management.